Pogorelov estimates for a class of fully nonlinear equations. (November 2021) - Chen, Xiaojuan; Lu, Wei; Tu, Qiang; Xiang, Ni
Abstract: In this paper, we give Pogorelov estimates for a general class of non-degenerate fully nonlinear equations and the corresponding degenerate equations by using a priori estimates.